Age in Children's Literature: Navigating Methodologies (KULT_online, 2024)
Age in David Almond’s Oeuvre analyzes the works of David Almond, known for his versatility in writing for both children and adults. Each chapter investigates intersecting research questions concerning the construction of age, presenting distinct insights into Almond’s literary repertoire. Ranging from autobiographical exploration to digital humanities methodologies, the review underscores the diverse analytical approaches utilized within contemporary children’s literary criticism.